1979
DOI: 10.1111/j.1365-3180.1979.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humidity and moisture stress on glyphosate control of Cyperus rotundus L.*

Abstract: Summary: Glyphosate at 2 kg/ha was more effective in reducing regrowth of purple nutsedge (Cyperus rotundus L.) scapes at 90% than at 50% relative humidity (r.h.), and more effective at −2 bars than at −11 bars of plant water potential. Regrowth of treated plants subjected to water potentials of −1 to −8 bars was reduced 54–60% while at −11 bars growth inhibition was only 34%. A time interval of as little as 8 h between application and excision was sufficient to give 47% reduction in regrowth at 90% r.h. None … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 12 publications
4
41
0
Order By: Relevance
“…was more evident at high temperatures (Tanipat and Adkins 1992). The adverse drought effect on glyphosate applied to purple nutsedge (Cyperus rotundus L.) was partly alleviated by high RH, which could be attributable to enhanced herbicide translocation under high RH (Chase and Appleby 1979). Similar results were obtained when poverty brome (Bromus sterilis) was treated with metoxuron [3-(3-chloro-4-methoxyphenyl)-1,1-dimethylurea] (Blair et al 1983).…”
supporting
confidence: 72%
“…was more evident at high temperatures (Tanipat and Adkins 1992). The adverse drought effect on glyphosate applied to purple nutsedge (Cyperus rotundus L.) was partly alleviated by high RH, which could be attributable to enhanced herbicide translocation under high RH (Chase and Appleby 1979). Similar results were obtained when poverty brome (Bromus sterilis) was treated with metoxuron [3-(3-chloro-4-methoxyphenyl)-1,1-dimethylurea] (Blair et al 1983).…”
supporting
confidence: 72%
“…The environmental conditions of central and southwestern Nebraska (predominant Palmer amaranth area) could also influence glyphosate performance. Glyphosate efficacy is reduced in several weeds under water stress and low‐humidity conditions . Adkins et al reported that glyphosate efficacy on Avena fatua and Urochloa panicoides was reduced under water stress combined with high temperatures, typical conditions found in central and southwestern Nebraska.…”
Section: Resultsmentioning
confidence: 99%
“…While applications at the R4 and R5 stages of growth occurred when peanut was entering full pod to beginning seed, respectively. Previous research has indicated that glyphosate was translocated through chains of purple nutsedge tubers (Chase and Appleby, 1979;Elmasry and Rehm, 1977;Zandstra and Nishimoto, 1977) as well as other species (Duke et al, 2003). Thus, it is theorized that glyphosate would be translocated to peanut pods and seed as they develop.…”
Section: Resultsmentioning
confidence: 99%